Telomerase reverse transcriptase germline mutations and hepatocellular carcinoma in patients with nonalcoholic fatty liver disease. (4th July 2017) - Donati, Benedetta; Pietrelli, Alessandro; Pingitore, Piero; Dongiovanni, Paola; Caddeo, Andrea; Walker, Lucy; Baselli, Guido; Pelusi, Serena; Rosso, Chiara; Vanni, Ester; Daly, Ann; Mancina, Rosellina Margherita; et al.
Abstract: In an increasing proportion of cases, hepatocellular carcinoma (HCC) develops in patients with nonalcoholic fatty liver disease (NAFLD). Mutations in telomerase reverse transcriptase (hTERT) are associated with familial liver diseases. The aim of this study was to examine telomere length and germline hTERT mutations as associated with NAFLD‐HCC. In 40 patients with NAFLD‐HCC, 45 with NAFLD‐cirrhosis and 64 healthy controls, peripheral blood telomere length was evaluated by qRT‐PCR and hTERT coding regions and intron–exon boundaries sequenced. We further analyzed 78 patients affected by primary liver cancer (NAFLD‐PLC, 76 with HCC). Enrichment of rare coding mutations (allelic frequency <0.001) was evaluated by Burden test. Functional consequences were estimated in silico and by over‐expressing protein variants in HEK‐293 cells. We found that telomere length was reduced in individuals with NAFLD‐HCC versus those with cirrhosis ( P  = 0.048) and healthy controls ( P  = 0.0006), independently of age and sex. We detected an enrichment of hTERT mutations in NAFLD‐HCC, that was confirmed when we further considered a larger cohort of NAFLD‐PLC, and was more marked in female patients ( P  = 0.03). No mutations were found in cirrhosis and local controls, and only one in 503 healthy Europeans from the 1000 Genomes Project (allelic frequency = 0.025 vs. <0.001; P  = 0.0005). Mutations with predicted functional impact, including the frameshift Glu113Argfs*79 and missense Glu668Asp, cosegregated with liver disease in two families. Three patients carried missense mutations (Ala67Val in homozygosity, Pro193Leu and His296Pro in heterozygosity) in the N‐terminal template‐binding domain ( P  = 0.037 for specific enrichment). Besides Glu668Asp, the Ala67Val variant resulted in reduced intracellular protein levels. In conclusion, we detected an association between shorter telomeres in peripheral blood and rare germline hTERT mutations and NAFLD‐HCC. Abstract : Telomere length was reduced in individuals who developed hepatocellular carcinoma in nonalcoholic fatty liver (NAFLD‐HCC) versus those with cirrhosis and healthy controls, independently of age and sex. We detected an enrichment of hTERT mutations in NAFLD patients affected by primary liver cancer, predominantly in females and specifically in the N‐terminal template‐binding domain. In conclusion, shorter telomeres and enrichment of hTERT rare germline mutations are associated with NAFLD‐HCC.